Dissolution of Calcium Ion from Human Enamel Treated With Zamzam Water in Comparison with Sodium Fluoride (Mustansiria Dental Journal, 2018)
Zamzam water has scientifically been proven to contain high concentration ofcalcium, magnesium, fluoride and many other minerals. This study aimed to test theability of zamzam water to increase the resistance of enamel surface against aciddissolution compared to sodium fluoride. Teeth sample of 15 maxillary first premolarswere randomly divided into 3 groups, study group treated with zamzam water, controlpositive treated with sodium fluoride and control negative treated with deionizedwater. The treatment lasted for two minutes once daily for 20 days interval. Then theconcentration of the dissolved calcium ion in the etching solution of 2N HCl wasmeasured by flame atomic absorption spectrometer. The amount of the releasedcalcium ion from zamzam water treated group was lesser than that released fromsodium fluoride treated group. However the difference was statistically notsignificant. A highly significant more calcium was dissolved from the water controlgroup compared with the mentioned agents P